THE EFFECTIVENESS OF ALOE VERA GEL AS A NATURAL GROWTH PROMOTER ON THE SUCCESS OF GRAFTING HONEY MANGO SEEDLINGS (Mangifera Indica): EFEKTIVITAS GEL LIDAH BUAYA SEBAGAI ZPT ALAMI TERHADAP KEBERHASILAN GRAFTING BIBIT MANGGA MADU (Mangifera Indica) - Maghfirah; Mizar Liyanda; Sri Agustina; Ayu Maharani (PT. ROCE WISDOM ACEH, 2025)
The development and improvement of mango plant quality can be achieved by providing high-quality mango seedlings in large quantities, in a short time, and at an affordable price. Vegetative propagation is an alternative method for obtaining high-quality seedlings, one of which is through grafting. This study aims to assess the effectiveness of applying aloe vera gel as a natural growth regulator (NGR) on scions for the success of grafting honey mango seedlings. The study was conducted at the experimental farm of the Indonesian Polytechnic of Venezuela in Cot Suruy Village, Ingin Jaya Sub-district, Aceh Besar District, from May to July 2024. The study utilized simple linear regression analysis. The observed parameters werestem height, stem diameter, and the number of leaves. The results of the ANOVA F-test analysis showed that treatments M0, M1, and M3 had an F-table value greater than the F-calculated value, indicating that the regression model was not statistically significant. However, treatment M2 had an F-table value smaller than the F-calculated value.